Development of Skill Assessment Instrument Service Volly 6th Grade in Physical Education - Moh. Noer; Ali Maksum; Anung Priambodo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research aims to develop instruments for assessing lower and upper service engineering skills in volleyball games for 6th-grade students in elementary schools. This research uses research and development methods, with the following development steps: (1) information gathering in the field, (2) analyze the information collected, (3) developing initial products, (4) expert validation and revision, (5) small-scale trials and revisions, (6) large-scale trials and revisions, (7) manufacturing of final products. The subject of this research is 6th-grade students of elementary students. Data analysis for the validity test was carried out with CVR (content validity ratio) and reliability using Alpha Cronbach. This research resulted in a handbook of instrument assessment tools for service techniques of lower and upper service in volleyball games for 6th-grade elementary school students, which contained instructions for use, student assignments sheets, assessment guidelines, assessment rubrics, and scoring tables, which have high validity. (1) And under service reliability initial attitude: r = 0.975, implementation: r = 0.961, follow-up motion: r = 0, 955. Upper Service for initial attitude: r = 0.961, implementation: r = 0.974, follow-up motion: r = 0.989.